2005
DOI: 10.1111/j.1365-2141.2004.05352.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of platelet counting haematology analysers in severe thrombocytopenia and potential impact on platelet transfusion

Abstract: SummaryAlthough haematology analysers provide reliable full blood counts, they are known to be inaccurate at enumerating platelets in severe thrombocytopenia. If the thresholds for platelet transfusion, currently set at 10 · 10 9 /l, are to be further reduced, it is vital that the limitations of current analysers are fully understood. The aim of this large multicentre study was to determine the accuracy of haematology analysers in current routine practice for platelet counts below 20 · 10 9 /l. Platelet counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
122
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 24 publications
8
122
0
5
Order By: Relevance
“…This may not be representative of other causes of thrombocytopenia especially those which are immune mediated like immune thrombocytopenic purpura (ITP). This is a significant factor as the superiority of optical and impedance methods over each other has often been debated (5). Improvements of optical platelet counting over impedance methods were described using various other CBC analyzers (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may not be representative of other causes of thrombocytopenia especially those which are immune mediated like immune thrombocytopenic purpura (ITP). This is a significant factor as the superiority of optical and impedance methods over each other has often been debated (5). Improvements of optical platelet counting over impedance methods were described using various other CBC analyzers (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…However, these smaller studies did not use thrombocytopenic samples from patients with hematological malignancies; the samples were specifically selected with low counts from patients with autoimmune thrombocytopenia and myelodysplasia, which are disorders where impedance platelet counting is known to be problematic because of the presence of large platelets. Recent studies have now concluded that the current methods of optical platelet counting may not be superior to impedance counts for all patient populations (5,18). This study shows similar results with the counts obtained from LH750 impedance (with curve fit correction) based counter were more precise and accurate when compared with CDS-O counts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings were reported by Messias et al (2009). Nevertheless, the automatic analyzers can overestimate the platelet count, what may be related to poor sensitivity at levels below the normal range (Segal et al, 2005).…”
Section: Discussionmentioning
confidence: 99%